The Taegeukgi and the Maple Leaf: The Pursuit of South Korean Export Markets by Atomic Energy Canada Limited - Slater, Ian (Scientia Canadensis, 2009)
AbstractIn the 1980’s Canada’s nuclear technology company, Atomic Energy Canada Limited (AECL), designed and attempted to sell a next-generation, small-scale nuclear reactor called the Slowpoke Energy System (SES). AECL pursued export markets for the SES, of which the most promising was South Korea. The SES project was forced to compete for funding and this necessitated the formation of partnerships with private and public sector agents in South Korea. AECL’s experience in South Korea suggests that crown corporations are more commercially oriented than established policy scholarship admits, and that in some cases competitive forces work to blunt innovation rather than reward it.